Junctionless accumulation-mode SOI ferroelectric FinFET for synaptic weights - Singh R.; Mittal S.; Verma S. (My University, 2025)
In this work, a novel silicon-on-insulator (SOI) based junctionless-accumulation-mode (JAM) ferroelectric (FE) fin field effect transistor (FinFET) is proposed along with its fabrication process flow at a 3-nm node for synaptic weights. The proposed JAM FE FinFET device can be easily integrated with the fabrication flow of p-FinFET in SOI process flow. The proposed device can be easily incorporated into standard FinFET SOI technology and thus is very attractive with respect to previously proposed devices. Further, using a well-calibrated 3D TCAD simulation setup, we show that the device effectively replicates the behavior required for neuromorphic computing applications. The outcomes of the proposed study emphasize the significance of using the JAM FE FinFET as a synaptic weight device that exhibits a 76 % higher nonvolatile conductance range in the ON-state over existing junctionless and conventional FE FinFET devices. Our simulations show that the proposed device offers continuous linear conductance variation and symmetric switching characteristics, which are essential for neuromorphic applications. © 2024 Elsevier Ltd